2014
DOI: 10.1111/tct.12193
|View full text |Cite
|
Sign up to set email alerts
|

Annual planning meetings: views and perceptions

Abstract: The main benefits of APMs were trainees feeling supported in their training and better informed regarding career options. APMs would be of value to all specialties to enable annual formative assessment to be undertaken at a different time to the summative assessment process. APMs facilitate reflection on learning needs, and the formulation of personal development plans and career goals for trainees. Trainees felt that the APM was a helpful formative assessment process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…We found no estimate of what proportion of trainees attend a meeting with the panel, although the literature suggests that only some do. 13,53 For trainees who do attend, the research suggests that the separation of the Annual Review of Competence Progression decision-making process from feedback/feedforward may not always be clear. 29,54 Where feedback is provided, trainees can perceive it as unhelpful, negative or even confrontational.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no estimate of what proportion of trainees attend a meeting with the panel, although the literature suggests that only some do. 13,53 For trainees who do attend, the research suggests that the separation of the Annual Review of Competence Progression decision-making process from feedback/feedforward may not always be clear. 29,54 Where feedback is provided, trainees can perceive it as unhelpful, negative or even confrontational.…”
Section: Resultsmentioning
confidence: 99%
“…We found no formal evaluations of interim reviews, although one study reported trainee and trainer experiences of attending a pilot Annual Planning Meeting three months before the Annual Review of Competence Progression, at which feedforward was provided. 53 Trainees in the pilot found the Annual Planning Meeting encouraging, non-confrontational and supportive, and liked that it did not rely on paperwork. Interestingly, trainers felt that only trainees in difficulty should have the meetings, but trainees who were progressing satisfactorily felt they gained from it, which supports the value of constructive, stretching feedback for all.…”
Section: Resultsmentioning
confidence: 99%